A Profile of non‐GM Crop Growers in the United States. (April 2016) - Kalaitzandonakes, Nicholas; Magnier, Alexandre
Summary: In the US, the management of coexistence between GM and non‐GM production systems has been left to market forces. Non‐GM growers in the US assume the responsibility and costs of coexistence and, in turn, are compensated in the form of price premiums paid for non‐GM crops. Using a producer survey we find that non‐GM corn and soybean growers in the US are commercial farmers not much different in size, asset ownership and demographic characteristics to farmers that only grow GM crops. Non‐GM growers seem to self‐select and participate in non‐GM production because they have fields that are sufficiently isolated and enough storage and labour to facilitate segregation. They grow non‐GM crops primarily to improve farm profitability, diversify and manage financial risk. Importantly, coexistence issues are not perceived to be major constraints by most non‐GM growers and even by a significant share of farmers who do not produce non‐GM crops. This is an important insight as farmers' perceptions are shaped within the context of the widespread adoption of GM crops in most US corn and soybean production regions. Furthermore, these views do not seem to suggest the presence of market failure in ensuring the coexistence of GM and non‐GM corn and soybean production in the US. Abstract : In the US, the management of coexistence between GM and non‐GM production systems has been left to market forces. Non‐GM growers in the US assume the responsibility and costs of coexistence and, in turn, are compensated in the form of price premiums paid for non‐GM crops. Using a producer survey we find that non‐GM corn and soybean growers in the US are commercial farmers not much different in size, asset ownership and demographic characteristics to farmers that only grow GM crops.